Technical and Economical Study on Increasing Oil Production in Old Wells (Traditional) by Performing Well Maintenance in the CP Field - Ardi Alfarizi; Nur Suhascaryo; Boni Swadesi (Journal of Petroleum and Geothermal Technology, 2023)
The CP field is an brown field with a production potential of 2,185 BOPD. However, the realization of CP Field production in the first semester was 1,931 BOPD (88.4% of the production target). From Low & Off data for the period from January to September 2020, it was found that the biggest problem contributing to LPO (Lost Production Opportunity) was caused by artificial lift wells and reduced production from old (traditional) wells.Several solutions can be done in order to solve the problem. Among them is by carrying out well maintenance, both those experiencing a decline in production or wells that have the potential to be activated. By implementing this, it is hoped that it will be able to maintain stability and even increase oil production and distribution through the old (traditional) well. The screening of reactivation well candidates is carried out with the technical evaluation stage and the economic evaluation stage. The engineering evaluation was carried out by analyzing the history of well production and analyzing the distribution map of the wells in the CP Field. Based on this data, 2 (two) candidate wells were obtained, namely LDK-38 and LDK-108. Then proceed with carrying out technical calculations of Rig capacity, namely by calculating Lifting Loads, Rotating Loads and Circulating Loads and continuing with the preparation of reactivation programs and economic calculations.Based on these calculations, it was found that the need for the Rig Capacity to carry out the reactivation work of the 2 (two) wells was 21 (twenty one) HP, so the Spindle Rig was chosen to do the work because the cost was more economical, which was Rp. 45,000,000, - for the work. per-well reactivation. Therefore, the total cost required for the reactivation of 2 (two) wells is Rp. 90,000,000,-. The reactivation program for the LDK-38 and LDK-108 wells resulted in additional production in the CP Field of + 21.73 BOPD or 5,932 bbl (January - September 2021). In addition, gross revenue of USD 572,000 was obtained (crude oil price of 49 USD/bbl).